Оцінка ефективності модернізації стандартними методами машин, що плавають - Єпіфанов, Віталій Валерійович; Бєлов, В. К.; Веретенніков, Євгеній Олександрович (НТУ "ХПІ", 2009)
Проведена оценка возможности модернизации плавающих машин стандартными методами (увеличение диаметра рабочего колеса водометного движителя) на примере бронетранспортера БТР-3Е. Определена максимальная скорость машины на плаву. Проведены расчеты для определения времени и соответствующего пути разгона машины до максимальной скорости.

The estimation of possibility upgradeability floating machine's upgradeability by standard methods is carried out. The method is shown by the example of BTR-3Е troop-carrier and includes in creasing the driving wheel’s diameter of the floating machine. The highest speed of the machine’s a float is calculated. Calculations the calculations for determination the time and the proper machine’s way of acceleration up to the highest speed are also offered.
Keywords: водомет; робоче колесо; сила тяги; плавучість